Preface: Structure and Function of Plant Canopies - HIROSE, T. (Ann Bot, 2004)
This section comprises a set of papers taken from those presented at a symposium held to commemorate the 50th anniversary of the Monsi–Saeki theory (1953), together with invited papers. The papers describe recent advances in the study of structure and function of plant canopies and are written by former students (and their collaborators) of Professors Monsi and Saeki. The topics cover construction and maintenance of efficient photosynthetic systems at leaf, individual plant and stand level. Canopy structure and function are analysed with respect to optimization and an evolutionarily stable strategy. A new translation of the original paper by Monsi and Saeki (1953) into English has been commissioned and is included in this section.